Gender Inequality Experienced by Jo March in the Film “Little Women (2019)” - Angelia, Feby; Widyaningrum, Agnes (Faculty of Language and Literature, University of Surakarta, 2024)
This research investigated the forms of gender discrimination experienced by the female character Jo March in the film